ChemInform Abstract: Synthesis of Cycloprodigiosin Identifies the Natural Isolate as a Scalemic Mixture. Issue 47 (November 2015) - Johnson, Rebecca E.; de Rond, Tristan; Lindsay, Vincent N. G.; Keasling, Jay D.; Sarpong, Richmond
Abstract: Both enantiomers of cycloprodigiosin are synthesized.